2005
DOI: 10.1016/j.febslet.2005.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Activation of phospholipase D by 8‐Br‐cAMP occurs through novel pathway involving Src, Ras, and ERK in human endometrial stromal cells

Abstract: We investigated the mechanism of 8-Br-cAMP-mediated phospholipase D (PLD) activation using a primary cell culture system of human endometrial stromal cells (ES cells). PLD activity was increased by the treatment of ES cells with 8-BrcAMP, maximally at 5 min. To determine whether the effects of 8-Br-cAMP on PLD occurred as a consequence of PKC activation, ES cells were preincubated for 15 min with RO320432 (1 lM) and GF109203X (1 lM), the PKC inhibitors, or they were pretreated for 24 h with phorbol myristate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Furthermore, it was shown that 8-bromo-cAMP stimulated PLD activity after activation of ERK 1/2 in primary cells of rat endometrium (38), supporting the hypothesis that PLD is downstream of ERK in that system. The mechanism whereby S1P activates PI3K and ERK 1/2 most likely involves an interaction of S1P with its Gi protein-coupled receptors, because preincubation of cells with PTX before treatment with S1P abolished the activation of these two pathways.…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, it was shown that 8-bromo-cAMP stimulated PLD activity after activation of ERK 1/2 in primary cells of rat endometrium (38), supporting the hypothesis that PLD is downstream of ERK in that system. The mechanism whereby S1P activates PI3K and ERK 1/2 most likely involves an interaction of S1P with its Gi protein-coupled receptors, because preincubation of cells with PTX before treatment with S1P abolished the activation of these two pathways.…”
Section: Discussionmentioning
confidence: 50%
“…Indeed, IGF-I activates SRC in mouse endometrial cells [68]. In addition, SRC is activated by the cAMP/ PKA signaling pathway in hESCs [76].…”
Section: D]pyrimidine (Pp1) and 4-amino-5-(4-chlorophenyl)-7-(t-butylmentioning
confidence: 99%
“…For instance, TSC and PLD are both modulated by mitogens (e.g., serum and insulin) [40][41][42][43][44][45][46] and TNFα. 15,47 The Ras-Raf-MEK-Erk pathway inhibits TSC2 via phosphorylation by either Erk 48,49 or a downstream kinase Rsk, 50 at the same time PLD activation by Ras [51][52][53][54] or Erk 54,55 has also been suggested. Most recently, our studies have uncovered a direct interaction between Rheb and PLD1.…”
Section: Pld1 As An Effector Of Rheb In Mtorc1 Signalingmentioning
confidence: 99%